Validity and Reliability of Indonesian Languages Version of Zung Self-Rating Depression Scale Questionnaire for Pulmonary Tuberculosis Patients: A Recent Update - Tirta Darmawan Susanto; Bambang Sutrisna; Asri C. Adisasmita; Annabella Vinsensa; S. N. Mega Tri Anggraini (Current Topics in Medicine and Medical Research Vol. 13, 2021)
Background: Patients with chronic disease, including tuberculosis, can be easily get depressed. Valid and reliable instrument needed to detect depression in Tuberculosis patients. The Indonesian language version of Zung Self-Rating Depression Scale questionnaire is needed to be proved as a valid and reliable instrument because so many Indonesian people are unable to read the English version. Objective: The purpose of this research is to obtain evidence on the validity and reliability of Indonesian language version of Zung Self-Rating Depression Scale questionnaire. Methods: The design of this study is cross sectional by giving Zung Self-Rating Depression Scale questionnaire that have been translated into Indonesian language to pulmonary tuberculosis patients. Characteristics of the population were were presented as mean, standard deviation, and percentage. Corrected Item-Total Correlation table was used for validity test and reliability test result was presented as Cronbach’s Alpha value. Results: Mean age of the population in this research is 47.75 ± 8.44 years old. Most of all have married (93%). Male and female pulmonary tuberculosis patients are 69% and 31% and 43% only graduated from elementary school. All 20 questions are valid because Corrected Item-Total Correlation values for all the questions are more than r table (>0,195). The questionnaire is also reliable with r Alpha value (Cronbach’s Alpha) 0,887, greater than r table value (>0,195). Conclusion: Indonesian language version of Zung Self-Rating Depression Scale questionnaire is a valid and reliable instrument to be used for detecting depression in adult pulmonary tuberculosis patients.